Black hole and neutron star mergers in galactic nuclei. Issue 1 (13th June 2019) - Fragione, Giacomo; Grishin, Evgeni; Leigh, Nathan W C; Perets, Hagai B; Perna, Rosalba
Abstract: Nuclear star clusters surrounding supermassive black holes (SMBHs) in galactic nuclei contain large numbers of stars, black holes (BHs), and neutron stars (NSs), a fraction of which are likely to form binaries. These binaries were suggested to form a triple system with the SMBH, which acts as a perturber and may enhance BH and NS mergers via the Lidov–Kozai mechanism. We follow-up previous studies, but for the first time perform an extensive statistical study of BH–BH, NS–NS, and BH–NS binary mergers by means of direct high-precision regularized N -body simulations, including post-Newtonian (PN) terms up to order PN2.5. We consider different SMBH masses, slopes for the BH mass function, binary semimajor axis and eccentricity distributions, and different spatial distributions for the binaries. We find that the merger rates are a decreasing function of the SMBH mass and are in the ranges ∼0.17–0.52, ∼0.06–0.10, and ∼0.04–0.16 Gpc −3  yr −1 for BH–BH, BH–NS, and NS–NS binaries, respectively. However, the rate estimate from this channel remains highly uncertain and depends on the specific assumptions regarding the star formation history in galactic nuclei and the supply rate of compact objects (COs). We find that${\sim } 10\!-\!20{{\ \rm per\ cent}}$ of the mergers enter the LIGO band with eccentricities ≳0.1. We also compare our results to the secular approximation, and show that N -body simulations generally predict a larger number of mergers. Finally, these events can also be observable via their electromagnetic counterparts, thus making these CO mergers especially valuable for cosmological and astrophysical purposes.